Do corporate site visits impact stock prices? - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2019)
We examine the stock price impact of corporate site visits using a unique dataset of site visits to listed firms in China. Our main findings are as follows. First, the market reaction around corporate site visits is statistically and economically significant and is stronger for group visits, visits conducted by mutual fund managers, visits covering accounting and finance topics, visits to firms with poor information environments, and visits to manufacturing firms. Second, the stock returns around site visits are positively associated with firms’ future performance. Third, the changes in visiting funds’ holdings are more predictive of firms’ future performance than those of non-visiting funds. Overall, our study contributes to the literature by presenting evidence on the stock price impact of corporate site visits, the variation of the impact, and the usefulness of site visits for visitors’ investment decisions.